'It's Torture for the Soul': The Harms of Image-Based Sexual Abuse. (August 2021) - McGlynn, Clare; Johnson, Kelly; Rackley, Erika; Henry, Nicola; Gavey, Nicola; Flynn, Asher; Powell, Anastasia
Beyond 'scandals' and the public testimonies of victim-survivors, surprisingly little is known about the nature and extent of the harms of 'image-based sexual abuse', a term that includes all non-consensual taking and/or sharing of nude or sexual images. Accordingly, this article examines the findings from the first cross-national qualitative study on this issue, drawing on interviews with 75 victim-survivors of image-based sexual abuse in the UK, Australia and New Zealand. We adopt a feminist phenomenological approach that permits more nuanced and holistic understandings of victim-survivors' experiences, moving beyond medicalised, trauma-based accounts of harm. Our analysis develops five interconnected accounts of the harms experienced, that we have termed social rupture, constancy, existential threat, isolation and constrained liberty. Our findings shed new light on the nature and significance of the harms of image-based sexual abuse that emphasises the need for more comprehensive and effective responses to these abuses.